Logical Analysis and Executive Performance - Branch, Melville C. (Academy of Management Journal, 1961)
Discusses the logical analytical ability of an executive to his management performance. Categories of the function of an executive; Importance of analytical abilities and responsibilities to business management; Discussion on intuition and subjective appraisal; Description of the analytical limitations of the human mind.